PROFITABILITY, COLLATERAL VALUE, FINANCING APPLICATION VALUE, LEVERAGE, NET WORKING CAPITAL AND CHARACTER ON DETERMINING THE CUSTOMERS FOR FINANCING IN ISLAMIC BANKS CATEGORIZED BY ETHNIC CHINESE, INDIGENOUS PEOPLE, MUSLIM AND NON-MUSLIM - Jayendati, Rabita Asri; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2018)
This study was involved by the NPF of islamic banks almost close to the threshold, 5%. One of aspects of the indication of increasing the NPF is the account officer of islamic banks innacuary to lending the financing to the customers that effected to bad credit. The aim of this study was to see the influence of profitability, collateral value, credit submission value, leverage, net working capital and character on determining the financing customers in islamic banks catogorized by ethnic chinese, indigenous people, muslim and non-muslim. The object of research used in this study is the account officer of Sharia Commercial Banks and Sharia Financing Banks in the City of Semarang as many as 52 account officers divided into 10 banks. The analytical method used is conjoint analysis to determine the influence and value of interest preferences from each account of a Sharia Commercial Banks and Sharia Financing Banks officer in the City of Semarang. Based on the results of the study for conjoint analysis shows that the value of interest preferences according to the overall respondents, the characters are in the first place witimportance values of 36.877%, leverage is second at 14.813%, the value of collateral in the third place at 12.461%, net working capital in the fourth place at 12.443%, the value of credit submission was fifth at 12.337% and the last was profitability which amounted to 11.069%.